Flame-Retardant and Tensile Properties of Polyamide 12 Processed by Selective Laser Sintering - Glaskova-Kuzmina, Tatjana; Dejus, Didzis; Jātnieks, Jānis; Kruuv, Partel-Peeter; Lancere, Linda; Kobenko, Stepans; Sarakovskis, Anatolijs; Zolotarjovs, Aleksejs (MDPI, 2022)
Composite materials are becoming widely applied in fire-critical conditions such as, e.g., aviation interior parts. Environmental considerations motivate the use of additive manufacturing due to the decrease of polymer wastes, and therefore additional fuel sources. The aim of this work was to evaluate the effect of printing direction on flame retardancy and the tensile properties of 3D-printed test samples of polyamide 12 manufactured by selective laser sintering. The effects of printing parameters on the flammability of 3D-printed samples were investigated using vertical burn tests with varied specimen thicknesses and printing directions. It was found that these effects were substantial for the flammability at a low thickness of the test samples. No significant effects of printing direction were revealed for the tensile characteristics of polyamide 12. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.
This research was funded by the European Regional Development Fund within Measure 1.1.1.1 “Industry-Driven Research” of the Specific aid objective 1.1.1 “To increase the research and innovation capacity of scientific institutions of Latvia and their ability to attract external funding by investing in human resources and infrastructure” of the Operational Program “Growth and Employment” (Project No. 1.1.1.1/19/A/143). A.S. and A.Z. are grateful to funding received from the European Union Horizon 2020 Framework programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; additive manufacturing; anisotropy; flame-retardant properties; polyamide 12; selective laser sintering; tensile properties; vertical burn test